Dampak Pencemaran Mikroplastik di Ekosistem Laut terhadap Zooplankton : Review - Mardiyana; Ari Kristiningsih (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
Microplastics pollution is one of the global problems. Plastic garbage entry in the ocean either intentionally or unintentionally and willbe degraded into microplastics. Microplastics size is small and float in water coloumn so make it easy to ingested by marine organisms,one of which is zooplankton. Zooplankton ingested microplastics and may impact upon zooplankton also the ecosystem. Microplastics can influence the fucundity, the feeding capacity, impact on digestion system, faecal pellet properties,and also provide accute and chronic effects on zooplankton. Impact on marine ecosystems allow microplastics transfers through food chain (trophic transfer) because of zooplankton have an important role in ecosystems. This review summarized the current knowledge about distribution and degradation of microplastics, ingestion of microplastics by zooplankton, the impact on zooplankton and also to the marine ecosystems. This study is important to provide basic information to researchers in marine resources management.